PELAKSANAAN TEKNIK PEMANDUAN DI URBANITAS TOUR AND TRAVEL PEKANBARU - Resky Harianto; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This Research aims to know about the Implementation of Guiding Technique at Urbanitas Tour and Travel Pekanbaru. This Research was used qualitative method with descriptive approach to describe and explain the condition that happened by collecting the data and information on the field. And the Informant key in this research was 1 chief executive officer and also become a Tour Leader during a Tour. and 3 employees of urbanitas tour and travel pekanbaru and also becom a Tour Leader during a tour. in this research, the technique to collecting the data used interview,observation and documentation technique. Based on the result of the research, can be concluded that the Tour Leaders at Urbanitas Tour and Travel Pekanbaru have done almost all the thing that refer to the theory that used. Buat there was also the thing that haven’t done by the tour leaders.Key words : Implementation, Guiding Technique